FAKTOR YANG BERHUBUNGAN DENGAN ADOPSI PETERNAK SAPI PERAH TENTANG TEKNOLOGI BIOGAS DI KABUPATEN ENREKANG SULAWESI SELATAN - Yusriadi, Yusriadi (Journal Galung Tropika, 2012)
This study analysed factors associated with adoption dairy farmer to biogas tecnology. There were 39 dairy cattle farmers in Enrekang Regency, Sulawesi Selatan that used biogas technology as research sample. Data were analysed by multiple correlation procedure using excel 2007 program. Research results showed that factors related to adoption of biogas technology were age, education background, income, experience, number of livestocks, number of families, contact with famers, contact with extension agent, digester distance to the kitchen, ability to obtains information, time gap to knew biogas until application, and motivation. The coefficiants relations of the famers characteristics and their adoption were 0.57 respectively.